2013
DOI: 10.1111/srt.12008
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance spectroscopy as a potential adjunct diagnostic tool for cutaneous melanoma

Abstract: Background: Previous studies have shown statistically significant differences in electrical impedance between various cutaneous lesions. Electrical impedance spectroscopy (EIS) may therefore be able to aid clinicians in differentiating between benign and malignant skin lesions. Objectives: The aim of the study was to develop a classification algorithm to distinguish between melanoma and benign lesions of the skin with a sensitivity of at least 98% and a specificity approximately 20 per cent higher than the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 42 publications
0
59
2
4
Order By: Relevance
“…EIS measurements on AMLs showed lower specificity compared with previous studies on EIS [57]. This may be due to the fact that the inclusion criteria in this study were different and that the sample size was smaller.…”
Section: Resultscontrasting
confidence: 62%
See 3 more Smart Citations
“…EIS measurements on AMLs showed lower specificity compared with previous studies on EIS [57]. This may be due to the fact that the inclusion criteria in this study were different and that the sample size was smaller.…”
Section: Resultscontrasting
confidence: 62%
“…The system measures bio-impedance of the skin at 35 different frequencies, logarithmically distributed from 1.0 kHz to 2.5 MHz, at four different depths utilizing 10 permutations. More exact details on how EIS measurements are performed have been published earlier [6,7]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, they reported that the system achieved sensitivity as high as 98.1% and speci city as high as 24.5% in a trial of 577 lesions including 103 melanomas [23]. Impedance measurement is generally lower in cost than optical measurement.…”
Section: Impedance Measurementsmentioning
confidence: 99%